Development of PBL-Based E-Modules on Work and Energy Materials Integrated with Nutrition to Improve Cognitive Learning Outcomes of Class X Students - Mulyanengsih, Ratu; Juita Nurhidayah, Isna; Dzakiruddin, Muhammad; Crosita Octaria, Yessi (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2023)
Abstract, Almost one third of Indonesian adolescents aged 15-18 years old are stunted, while many also have overweight and obesity problem. Nutrition education can be done by integrating nutritional information and concepts into certain subjects, one of which is physics. Subject in physics which in line with the concept of nutrition are work and energy. In work and energy subject, it discusses the concept of the relationship between work, energy, the law of conservation of energy, the concept has strong relationship with nutrition which is a source of energy needed to do work. This research is a development research with the ADDIE model, which has 5 stages, Analyze; (2) Design; (3) Develop; (4) Implement; and (5) Evaluate [19]. The purpose of this study is